Angiosarcoma arising in sclerodermatous skin - Puizina-Ivić, Neira (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2005)
We report a case of cutaneous angiosarcoma in a 77-year-old female patient with systemic sclerosis. The tumor developed around a large telangiectasia in the left temporal region. Later on, extensive asymptomatic redness and edema with several nodules over the whole left side of the face developed. Since theconservative therapy failed to produce any improvement, a diagnostic skin biopsy was performed. The pathohistological diagnosis was moderately differentiated angiosarcoma. The patient was treated with a combination of chemotherapy and electron beam irradiation. Despite a notable cutaneous improvement, the control check-up revealed the presence of metastases of the lung and liver. This is the first report of cutaneous angiosarcoma occuring insclerodermatous skin. The possible pathogenesis of this rare tumorogenic transformation of soft tissues is discussed.
Keywords: Aged; angiosarkom; Complications; dermatologija; Diagnosis; Hemangiosarcoma; Hemangiosarkom; kožne bolezni; Neoplasm Metastasis; Novotvorba, metastaza; Pathology; rak (medicina); Scleroderma, Systemic; Sklerodermija sistemska; Starostniki; Telangiectasis; Teleangiektazija; Therapy